Escritas de liberdade: memória, subjetividade e emancipação em Luiz Gama e Mahommah Gardo Baquaqua - Gustavo de Oliveira Bicalho (2022)
This work aims to investigate the textual reworking of subjectivity and memory as practices of emancipation and freedom in the texts of Mahommah Gardo Baquaqua (1824?-??) and Luiz Gama (1830-1882). Considering these are the only known authors to have gone through slavery in Brazil, we will try to demonstrate how their texts contribute to the formation of a literary corpus of the Black Atlantic. For this purpose, we will seek to investigate two main hypotheses. Firstly, that these subjects produce themselves as authors and intellectuals-witnesses by publishing books that, in different ways, stage a subjectivity freed from the stigma of slavery. Secondly, that such reenactments of the "self" between the private and the public spheres engender the writing of freedom as a "writing of us/knots" (the word for us in Portuguese is “nós”, which also means “knots”), both by the ties that it establishes with a transnational Afrodescendant collectivity, and by the obstruction of the processes of historical erasure and whitening assimilation that mark the cultural projects of the American nations of the nineteenth century. Starting from a dialogic and comparative perspective of biographical criticism, we will endeavor to study the texts produced by these authors in dialogue with their paratexts and their context of production and reception, aiming to understand how they contribute not only to the social emancipation of their authors, but also to the collective construction of an Africanized conception of freedom. We will closely study the poems of Primeiras trovas burlescas de Getulino, a book written and published by Luiz Gama in two editions (1859, 1861), in addition to the beginning of his trajectory as a journalist (1862-1869). In these writings, we will follow the creation of an Afrodescendant enunciation in-between personas and satirical masks, under which an ethical, aesthetic and political proposition for Brazil as a nation and state is revealed. Concurrently, we will propose a reading of The Biography of Mahommah Baquaqua, a book of autobiographical and testimonial content published in Detroit in 1854 by a man whose transatlantic narrative deviates from the traditional script of African-American slave narratives in a direction that merges Africa and freedom into corresponding terms.